Evaluation of Duration of Immunogenicity and Protective Efficacy of Improved Influenza Viral Vector–Based Brucella abortus Vaccine Against Brucella melitensis Infection in Sheep and Goats - Mailybayeva, Aigerim; Ryskeldinova, Sholpan; Zinina, Nadezhda; Zhou, En-Min; Renukaradhya, Gourapura J.; Tabynov, Kaissar (Frontiers in Veterinary Science, 2020)
In this study, we first evaluated the duration of a protective immune response against B. melitensis infection in non-pregnant sheep and goats immunized with an improved (by vaccine formulation and route of administration) commercial B. abortus vaccine based on influenza viral vectors expressing Brucella immunodominant Omp16, L7/L12, Omp19 or Cu-Zn SOD proteins (Flu-BA_Omp19-SOD). Sheep and goats in the vaccinated group were immunized thrice concurrently via the subcutaneous and conjunctival routes of administration at an interval of 21 days. Animals in the control group were administered with 20% Montanide Gel01 adjuvant in PBS in the same way. We showed that Flu-BA_Omp19-SOD vaccine in sheep and goats induces antigen-specific Th1 biased (IgG2a over IgG1) antibody response and T-cell and IFN-γ responses lasting over a period of one month post-last vaccination (PLV). The levels of protection against B. melitensis 16M infection (vaccination efficacy) in vaccinated sheep for a period of six months was 0-20% and in goats 20-40% compared to control challenge group. But the severity of B. melitensis 16M infection in Flu-BA_Omp19-SOD vaccinated sheep and goats during the entire period of observation revealed the infection index (P=0.001-P<0.0001) and Brucella colonization in lymph nodes and organs (P=0.04-P<0.0001) was significantly lower than control group. To conclude, Flu-BA_Omp19-SOD vaccine using improved formulation and administration method in sheep and goats provides augmented antigen specific humoral and T-cell immune response lasting only for 1 month PLV, and partial protection for 6 months against B. melitensis 16M infection.